Penerapan Akad Murabahah pada Produk MULIA di Pegadaian Jalancagak Menurut Perspektif Ekonomi Syariah - Raden Andriana Meirani; Ahmad Damiri; Jalaludin Jalaludin (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2020)
This research was conducted at Pegadaian Jalancagak Subang Regency. Pegadaian is one of the financial institutions that offers Logam Mulia investment services, one of which is called MULIA (Murabahah Logam Mulia For Abadi Investment). Product Mulia is a financing offer to customers for the purchase of gold bars produced by PT. Aneka Tambang (ANTAM). This study aims to determine how MULIA product provisions, the application of the murabaha contract on MULIA products and the impact of MULIA products for pawnshops and the community. This type of research is qualitative using descriptive analysis method. Data sources used include primary and secondary data. From the results of the discussion the researchers found that there were several provisions in the application of the MULIA product murabahah in Pegadaian Jalancagak that were not in accordance with the provisions of the Shari'a, including; first concerning the object of the contract or Marhun which was not raised or did not exist during the contract. Second, the sanctions that are permitted according to the Shari'a are applicable to customers who are capable but neglect or postpone delay of payment but do not apply to customers who are truly unable to pay, but in its application at Jalancagak pawnshop requires all customers to receive sanctions or pay fines if unable pay without exception. Third, in the application of sanctions / fines regarding funds generated from fines input as corporate income, which according to Shari'a provisions should be intended for social funds